Early physiological regulation predicts the trajectory of externalizing behaviors across the preschool period. Issue 7 (7th June 2014) - Perry, Nicole B.; Nelson, Jackie A.; Calkins, Susan D.; Leerkes, Esther M.; O'Brien, Marion; Marcovitch, Stuart
ABSTRACT Early assessments of children's physiological functioning are shown to predict subsequent developmental outcomes. However, individual changes that occur in the development of physiological systems may be associated with the pattern of change in behavior across time. Thus, we examined change in respiratory sinus arrhythmia (RSA), an index of physiological regulation, as a time‐varying predictor in order to assess whether RSA change at ages 3, 4, and 5 uniquely influenced the trajectory of externalizing behaviors from age 3 to 5. Results indicated that only at age 3 was RSA change significantly associated with decreases in externalizing behaviors over time. RSA change scores at ages 4 and 5 were unrelated to trajectories of externalizing behavior, suggesting that the ability to physiologically regulate by age 3 may contribute to the development of skills that facilitate more control over behavior throughout preschool, and therefore may be more strongly associated with the pattern of change in externalizing behaviors than later physiological regulation. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1482–1491, 2014.